Trials and Triumphs of School Leaders with Diverse Sogie in Managing Workplace Conflicts - Junee L. Abetria; Rainier T. Cristobal; Delon Angelo L. Dela Cruz (Future Science / FSH-PH Publications, 2026)
This study explores the experiences of school leaders in Masbate Province who identify with diverse Sexual Orientation, Gender Identity, and Expression (SOGIE). It examines their trials, triumphs, and how they manage conflicts within workplace learning environments. Using purposive sampling and a qualitative, phenomenological methodology, the study emphasizes real-life challenges caused by institutional discrimination, bias, and communication breakdowns. Despite these challenges, these leaders consistently employ inclusive leadership approaches to foster equal and supportive school environments, demonstrating emotional intelligence and resilience. Findings reveal that SOGIE-diverse leaders face challenges rooted from both organizational structures and interpersonal relations, often worsened by exclusion. They do, however, address issues using tactics such as private talks, professional development, emotional de-escalation, and strict protocol adherence. Their leadership includes empathy, adaptability, and a strong commitment to diversity. Creating inclusive school cultures and engaging the broader community is also crucial for effective conflict resolution. While institutional initiatives, such as Project PATAS and Gender and Development (GAD) programs, aim to support inclusivity, their effectiveness is limited by inconsistent implementation and weak accountability. The study emphasizes the importance of policy adjustments and continued leadership training for persons from SOGIE-diverse backgrounds. These leaders play a vital role in encouraging respect, diversity, and inclusivity, which benefits both educators and learners.